Transformational and Nurturing Leadership Practices in Building Human Resource Capacity in Schools - Nasrullah, Muh. (ASHA Publishing, 2025)
This study explores the role of educational leadership in enhancing human resource capacity within schools through a qualitative, exploratory design. Drawing on semi-structured interviews with school leaders and senior teachers from both high-performing and underperforming secondary schools, the research investigates how leadership practices influence teacher motivation, professional development, and organizational resilience. Thematic analysis revealed four key themes: the impact of transformational leadership on teacher engagement, the significance of nurturing leadership in promoting staff well-being, the contextual factors that mediate leadership effectiveness, and the influence of gender on leadership perception and experience. Findings indicate that effective leadership in education is deeply relational and context-sensitive. Transformational and nurturing leadership practices were found to foster trust, collaboration, and professional satisfaction, particularly in challenging school environments. Moreover, gender dynamics shaped how leadership styles were enacted and received, revealing underlying cultural expectations that influence leadership efficacy. These insights underscore the importance of human-centered and context-aware leadership development programs that emphasize emotional intelligence, inclusivity, and adaptability. The study contributes to the broader discourse on educational improvement by framing human resource capacity as a product of thoughtful, responsive, and inclusive school leadership.